iOMTARA (INTERIOR OMAH NUSANTARA) : APLIKASI ROOM TOUR DENGAN MENGGUNAKAN TEKNOLOGI VIRTUAL REALITY SEBAGAI MEDIA PENGENALAN PARIWISATA RUMAH TRADISIONAL NUSANTARA - Dhesti Anggraini, Swastika; Sidyawati, Lisa; Ponimin, Ponimin; Ujang, Norsidah (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
The role of information technology is the main thing that must be fulfilled to support activities in various fields of life, including the promotion of tourism. One of the developing information is Virtual Reality technology. iOMTARA (interior of Omah Nusantara) is a room tour application development that was created as a media for the introduction and promotion of tourism in the Nusantara. The 3D objects displayed in this application are Joglo Yogyakarta Indonesia's traditional house and Melaka Malaysia’s traditional house. Both of them were chosen because currently the traditional house no longer functions as a residence but also as a tourist attraction for both foreign and domestic tourists. This application was developed using interactive visual methods such as virtual worlds that make users feel like they are getting the same information as the experience of entering the space in the real houses. The application of building 3D objects from houses is followed by making video interactions using virtual reality. The final stage, this application will be incorporated into a mobile phone based on the Android operating system so that it can be used easily by the people. The application design method begins with a preliminary study of qualitative methods to obtain data directly in the field. Then the data is used to designing virtual reality in the IOMTARA Room Tour application. The result of making this application is the design of an iOMTARA application that uses Virtual Reality technology and can be used on mobile phone based on the Android system. It is expected that with this application, the people is more familiar with tourism objects in the Nusantara, especially the Joglo Yogyakarta Indonesia’s traditional house and the Melaka Malaysia’s traditional house.